The Vienna writers circle - Maetis, J. C. (Mira, 2023)
"Spring, 1938: Café Mozart in the heart of Vienna is beloved by its clientele, including cousins Mathias Kraemer and Johannes Namal. The two writers are as close as brothers. They are also members of Freud's Circle--a unique group of the famed psychiatrist's friends and acquaintances who once gathered regularly at the bright and airy café to talk about books and ideas over coffee and pastries. But dark days are looming. With Hitler's annexation of Austria, Nazi edicts governing daily life become stricter and more punitive. Now Hitler has demanded that the "hidden Jews" of Vienna be tracked down, and Freud's Circle has been targeted. The SS aims to use old group photos to identify Jewish intellectuals and subversives. With the vise tightening around them, Mathias and Johannes's only option appears to be hiding in plain sight, using assumed names and identities to evade detection, aware that discovery would mean consignment to a camp or execution. Faced with stark and desperate choices, Mathias, Johannes, their families and friends all find their loyalties and courage tested in unimaginable ways. But despite betrayal, heartache and imprisonment, hope remains, and with it, the determination to keep those they love alive, and Mathias and Johannes at the same time discovering that what originally condemned them--their writing--might also be their salvation"--